Metabolic crossroads in insulin resistance: exploring lipid dysregulation and inflammation - Saadati, Saeede; Godini, Rasoul; Reddy, Anjana; Teede, Helena; Mousa, Aya (Frontiers in Immunology, 2025)
Insulin resistance is a central pathological feature of several chronic metabolic disorders, including obesity, type 2 diabetes, polycystic ovary syndrome, and cardiovascular disease. While its pathogenesis is multifactorial, lipid dysregulation and chronic low-grade inflammation are recognised as two major, interconnected processes that impair insulin action across multiple tissues. This review summarises core mechanistic themes linking these processes, with a focus on three key signalling pathways that are particularly relevant to metabolic regulation and to the interplay between lipid metabolism, inflammation, and insulin action: phosphoinositide 3-kinase/protein kinase B, AMP-activated protein kinase, and c-Jun N-terminal kinase. Dysregulated lipid metabolism, including the accumulation of bioactive intermediates such as diacylglycerols and ceramides, disrupts insulin signalling, promotes lipotoxicity and adipose tissue dysfunction, and triggers inflammatory cascades. In parallel, inflammatory mediators, including cytokines, adipokines, and related signalling pathways, further impair insulin receptor function and exacerbate metabolic stress. Together, these processes form a self-reinforcing cycle that sustains insulin resistance and accelerates disease progression. Despite recent advances in delineating these mechanisms, critical gaps remain in defining tissue-specific effects, pathway interactions, sex-based differences, and the roles of lesser-studied lipid species and regulatory layers, highlighting priorities for future mechanistic research.